2016
DOI: 10.15376/biores.11.1.1796-1807
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Effectiveness of Complex Fire-Retardants on the Fire Properties of Ultra-low Density Fiberboard (ULDF)

Abstract: The preparation conditions of complex fire-retardant (FR) agents containing boron compounds (BF, X1), nitrogen-phosphorus compounds (NPF, X2), silicon compounds (SF, X3), and halogen compounds (HF, X4) for ultra-low density fiberboard (ULDF) were optimized using a response surface methodology. The effects and interactions of X1, X2, X3, and X4 on the fire properties of ULDF were investigated. An optimum char yield of 61.4% was obtained when the complex fire-retardant agents contained 33.9% boron, 27.2% nitroge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 25 publications
(37 reference statements)
0
9
0
Order By: Relevance
“…For example, the char yield of MF at 350 °C and 500 °C increased by 78.31% and 112.78%, respectively, compared with CF. These results indicated that the fire resistance of fiberboards is improved by complex fire-retardants, which improve the protection properties of the residues (Chen et al 2015b(Chen et al , 2016a. …”
Section: Effect Of Temperature On the Char Yield Of Ultra-low Densitymentioning
confidence: 86%
See 4 more Smart Citations
“…For example, the char yield of MF at 350 °C and 500 °C increased by 78.31% and 112.78%, respectively, compared with CF. These results indicated that the fire resistance of fiberboards is improved by complex fire-retardants, which improve the protection properties of the residues (Chen et al 2015b(Chen et al , 2016a. …”
Section: Effect Of Temperature On the Char Yield Of Ultra-low Densitymentioning
confidence: 86%
“…The mass loss of MF in the third stage was 9.7% higher than the CF, indicating that the complex fire-retardants prompted the decomposition of polymer toward carbonaceous residues. Additionally, the exothermic peak around 400.0 °C was obviously decreased, indicating the deflagration process in fiberboards was restrained by complex fire-retardants, which produce a synergistic effect between different compositions (Chen et al 2016a). In sum, the thermostability of the ULDFs was improved by complex fire-retardants.…”
Section: A B C Dmentioning
confidence: 95%
See 3 more Smart Citations